Palestinian hunger strikers in the Israeli settler-colonial and carceral system: Uniting inside and outside resistance, local and transnational solidarity - Daniele, G.; Borralho, J. P. (Journal of Holy Land and Palestine Studies, 2025)
This article analyses the interconnection of the resistance practice of hunger striking inside Israeli colonial prisons and forms of solidarity in support of Palestinian political prisoners, both local and transnational. Centered on the settler-colonial and carceral framework, our research examines the Israeli carceral power towards Palestinian society as a whole and, in detail, the use of administrative detention by Israel as one of the most powerful forms of collective punishment. We also look at Israel’s medical negligence that directly impacts life and death inside prisons. Based on fieldwork conducted in the West Bank and online interviews between 2022 and 2023, this article explores one of the most extreme forms of resistance used by Palestinian political prisoners, namely hunger strikes both individual and collective, that are supported by local and transnational solidarity. The interaction between resistance practices inside Israeli colonial prisons and diverse levels of solidarity generated outside prisons is a challenging new field of research to deal with in Palestine Studies, as it looks at the increasing potential of activists’ engagement in intersectional and transnational narratives.